Competitiveness of Creative Industries of Small and Medium Entrepreneurs of Handicraft Products - Rodhiah, .; Hidayah, Nur (KnE Social Sciences, 2021)
This study aimed to design an implementation strategy for evaluating the competitive advantage assessment of the APP model (asset/performance, potential, and process) in creative industries in the South Tangerang area of Indonesia. There were 20 respondents of small and medium industries who have handicraft businesses, such as batik, plait, accessories, midrib, and others. Participants were recruited by purposive sampling. Data were collected through observations, interviews, and focus group discussions. This research was qualitative in nature, and data were analyzed to assess competitive advantage based on the 3 P’s (potential, process, and performance). The research results can be used to develop the creative industry of the handicraft sector in South Tangerang, to increase the competitive advantage, preserve business activity and develop regional creative industrial centers in the potential handicraft sector. Keywords: creative industry in the handicraft sector, small and medium industry, potential excellence, performance process